2015
DOI: 10.3109/13506129.2015.1102131
|View full text |Cite
|
Sign up to set email alerts
|

The patient’s perspective on the symptom and everyday life impact of AL amyloidosis

Abstract: Symptoms can vary widely, but a core set of symptoms were common across patients. The conceptual model derived from this study can be used to ensure a patient-centered approach to drug development.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
41
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(43 citation statements)
references
References 15 publications
2
41
0
Order By: Relevance
“…14 Using published studies, patient and expert interviews, and patient blogs, Lin and colleagues developed a conceptual model of the manifestations of AL amyloidosis. 16 Many of the symptoms and impacts included in Lin and colleagues' conceptual model are similar to those of the current study. As data on patients' experience of ATTR accumulate, we recommend the development of a conceptual model for this form of amyloidosis.…”
Section: Discussionsupporting
confidence: 59%
See 1 more Smart Citation
“…14 Using published studies, patient and expert interviews, and patient blogs, Lin and colleagues developed a conceptual model of the manifestations of AL amyloidosis. 16 Many of the symptoms and impacts included in Lin and colleagues' conceptual model are similar to those of the current study. As data on patients' experience of ATTR accumulate, we recommend the development of a conceptual model for this form of amyloidosis.…”
Section: Discussionsupporting
confidence: 59%
“…Conceptual models have the potential to elucidate the effects of a disease helping to elaborate the causal relationships linking symptoms, functioning, health perceptions and quality of life. 15 A conceptual model can inform the development of patient-reported outcomes (PRO) measures for future clinical trials 16 and ultimately promote the design of effective treatments. 14 Using published studies, patient and expert interviews, and patient blogs, Lin and colleagues developed a conceptual model of the manifestations of AL amyloidosis.…”
Section: Discussionmentioning
confidence: 99%
“…Qualitative research indicates that patients with AL amyloidosis experience substantial burden that can lead to impairment in daily functioning [10, 11]. Furthermore, AL amyloidosis can lead to anxiety, frustration, and depression as patients grapple with the gravity and rarity of their condition [10, 12]. Although limited, quantitative studies provide evidence of deficits in both physical and mental aspects of HRQoL [13, 14].…”
Section: Introductionmentioning
confidence: 99%
“…Light chain amyloidosis (AL) is a disease with multi‐organ damage and a wide spectrum of presentations. Patients with AL often have delayed diagnosis and present with significant symptomatology, which may result in lower overall QOL . These issues can results in increased depression and anxiety in AL, one study showed rates of of anxiety and depression in AL of 37% and 46.7%, respectively,much higher than the general population .…”
Section: Introductionmentioning
confidence: 99%